Penanganan Stunting di Desa Teluk Sasah Kecamatan Seri Kuala Lobam Kabupaten Bintan - Sri Ambar Rinah; Diah Siti Utari; Billy Jenawi; Zunani Zunani (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Stunting is a multidimensional health problem that remains prevalent in Indonesia, including in Teluk Sasah Village, Seri Kuala Lobam District, thus requiring handling strategies through improved public services and community empowerment. The purpose of this research is to determine how stunting is addressed in Teluk Sasah Village, Seri Kuala Lobam District, Bintan Regency. This study employs a descriptive qualitative method using observation, in-depth interviews, and descriptive data analysis to illustrate public services and community empowerment in handling stunting in Teluk Sasah Village. The research findings reveal that stunting management in Teluk Sasah Village still faces major challenges related to the community’s limited economic conditions, parents’ low awareness of the importance of balanced nutrition and healthy parenting, as well as the suboptimal functioning of posyandu (integrated health posts) due to limited health personnel and supporting facilities. Although the village government has implemented various national programs such as supplementary feeding, nutrition education, and child growth monitoring, their effectiveness has not been optimal because of low community participation and weak coordination among stakeholders. Nevertheless, community empowerment through training, mentoring, and the utilization of local potential such as nutritious food cultivation is considered capable of raising awareness and fostering shared responsibility. This study concludes that improving the quality of public services and encouraging active community participation are key to reducing stunting rates in Teluk Sasah Village.